KEBEBASAN BERAGAMA: PERSIMPANGAN ANTARA HAK ATAU KEWAJIBAN? - Widianti, Alifia; Purba, Iman Pasu Marganda Hadiarto; Yani, Muhammad Turhan (Journal of Civics and Moral Studies, 2024)
The intersection of religious freedom as a right or obligation still requires in-depth study, where the state should be present in providing certainty regarding this matter. The formulation of the problem of this research is first, whether religious freedom also includes the freedom not to have a religion. Second, how is the positioning of religious freedom in Indonesia according to Pancasila and the constitution. The research method used in this study is qualitative descriptive based on postpositivism and is used to examine the intersection of religious freedom in real conditions using literature studies such as books, scientific journals and scientific articles. The conclusion of this study is that religious freedom is actually a basic right that cannot be reduced under any circumstances, especially in the forum internum. However, its validity in Indonesia becomes an obligation when it is based on Pancasila and the constitution of legislation which indicates that Indonesia is a God-fearing country. Thus, a middle ground can be taken in terms of the placement of religious freedom based on the principles of justice and applicable positive law.